Distributed computation as an economic system. - Huberman, Bernardo A.; Hogg, Tad (Journal of Economic Perspectives)
Economics is helpful for allocating computational resources to programs that run on computer networks. This is because computer networks can be viewed as a community of concurrent processes, or a “computational ecosystem.” As such networks grow, they become more analogous to human market economies because their processes face the same issues as individuals in a market—interactions, strategies, and lack of perfect knowledge. One of the main implications of this analogy is that economics may provide new ways to design and understand the behavior of distributed computer systems. A computational system built in accordance with market rules can allow the system as a whole to adapt to changes in the environment or disturbance to individual members.